PNPLA3, CGI‐58, and Inhibition of Hepatic Triglyceride Hydrolysis in Mice. Issue 6 (9th April 2019) - Wang, Yang; Kory, Nora; BasuRay, Soumik; Cohen, Jonathan C.; Hobbs, Helen H.
Abstract : A variant (148M) in patatin‐like phospholipase domain‐containing protein 3 (PNPLA3) is a major risk factor for fatty liver disease. Despite its clinical importance, the pathogenic mechanism linking the variant to liver disease remains poorly defined. Previously, we showed that PNPLA3(148M) accumulates to high levels on hepatic lipid droplets (LDs). Here we examined the effect of that accumulation on triglyceride (TG) hydrolysis by adipose triglyceride lipase (ATGL), the major lipase in the liver. As expected, overexpression of ATGL in cultured hepatoma (HuH‐7) cells depleted the cells of LDs, but unexpectedly, co‐expression of PNPLA3(wild type [WT] or 148M) with ATGL inhibited that depletion. The inhibitory effect of PNPLA3 was not caused by the displacement of ATGL from LDs. We tested the hypothesis that PNPLA3 interferes with ATGL activity by interacting with its cofactor, comparative gene identification‐58 (CGI‐58). Evidence supporting such an interaction came from two findings. First, co‐expression of PNPLA3 and CGI‐58 resulted in LD depletion in cultured cells, but expression of PNPLA3 alone did not. Second, PNPLA3 failed to localize to hepatic LDs in liver‐specific Cgi ‐ 58 knockout (KO) mice. Moreover, overexpression of PNPLA3(148M) increased hepatic TG levels in WT, but not in Cgi ‐ 58 KO mice. Thus, the pro‐steatotic effects of PNPLA3 required the presence of CGI‐58. Co‐immunoprecipitation and pulldown experiments in livers of mice and in vitro using purified proteins provided evidence that PNPLA3 and CGI‐58 can interact directly. Conclusion: Taken together, these findings are consistent with a model in which PNPLA3(148M) promotes steatosis by CGI‐58‐dependent inhibition of ATGL on LDs.